Do the Kinds of Achievement Errors Made by Students Diagnosed With ADHD Vary as a Function of Their Reading Ability?. (February 2017) - Pagirsky, Matthew S.; Koriakin, Taylor A.; Avitia, Maria; Costa, Michael; Marchis, Lavinia; Maykel, Cheryl; Sassu, Kari; Bray, Melissa A.; Pan, Xingyu
A large body of research has documented the relationship between attention-deficit hyperactivity disorder (ADHD) and reading difficulties in children; however, there have been no studies to date that have examined errors made by students with ADHD and reading difficulties. The present study sought to determine whether the kinds of achievement errors made by students diagnosed with ADHD vary as a function of their reading ability. The participants in this study were 91 students in the ADHD clinical validity standardization sample of the Kaufman Test of Educational Achievement–Third Edition (KTEA-3), as well as a control group of 63 students selected from the larger standardization sample. Students with ADHD and reading difficulties demonstrated a statistically significant greater amount of errors across tests of academic achievement. Findings from the study are discussed within the context of past research, as well as implications for the field of school psychology and practitioners.